Smart House Initiative for Enhancing Literacy and Empowering the Tubo Community in Ternate, North Maluku: Program Rumah Cerdas sebagai Upaya Peningkatan Literasi dan Pemberdayaan Masyarakat Tubo Ternate Maluku Utara - Agustang, Andi Tenripada; Rasyid, Rusman; Sudjud, Suratman; Muchsin, Sitti Busyrah; Umaternate, Desi; Umasangaji, Irfanto (Yayasan Ahmar Cendekia Indonesia, 2024)
This study explores the Smart House Program as a community service initiative aimed at enhancing literacy and empowering the Tubo community in Ternate, North Maluku. The program integrates literacy enhancement with community empowerment by focusing on three key areas: disaster mitigation literacy, digital literacy, and entrepreneurship development. A multi-faceted approach was employed, which included the construction of a Smart House as a literacy center, hands-on training in biofloc-based fish farming, and hydroponic vegetable cultivation. The program also involved the digital literacy training of community members, specifically targeting women in the local PKK (Family Welfare Movement) group. The results demonstrated a significant improvement in the community's ability to utilize digital platforms, an increase in disaster preparedness knowledge, and enhanced entrepreneurial skills, leading to improved productivity and economic resilience. This initiative presents a scalable model for addressing literacy and livelihood challenges in rural, disaster-prone areas. Abstrak Artikel ini mengeksplorasi Program Rumah Cerdas sebagai inisiatif pengabdian masyarakat yang bertujuan untuk meningkatkan literasi dan memberdayakan masyarakat Kelurahan Tubo di Ternate, Maluku Utara. Program ini mengintegrasikan peningkatan literasi dengan pemberdayaan komunitas melalui fokus pada tiga area utama: literasi mitigasi bencana, literasi digital, dan pengembangan kewirausahaan. Pendekatan multifaset digunakan, termasuk pembangunan Rumah Cerdas sebagai pusat literasi, pelatihan praktik dalam budidaya ikan berbasis bioflok, dan budidaya sayuran hidroponik. Program ini juga melibatkan pelatihan literasi digital bagi anggota masyarakat, khususnya perempuan dalam kelompok PKK (Pemberdayaan Kesejahteraan Keluarga) setempat. Hasil penelitian menunjukkan peningkatan yang signifikan dalam kemampuan masyarakat untuk memanfaatkan platform digital, peningkatan pengetahuan tentang kesiapsiagaan bencana, dan keterampilan kewirausahaan yang lebih baik, yang mengarah pada peningkatan produktivitas dan ketahanan ekonomi. Inisiatif ini menawarkan model yang dapat diperluas untuk mengatasi tantangan literasi dan mata pencaharian di daerah pedesaan yang rawan bencana.